Unraveling the diversity of hyphal explorative traits among Rhizophagus irregularis genotypes - Sun, Daquan; Rozmoš, Martin; Kokkoris, Vasilis; Kotianová, Michala; Hršelová, Hana; Bukovská, Petra; Faghihinia, Maede; Jansa, Jan (Mycorrhiza, 2024)
Differences in functioning among various genotypes of arbuscular mycorrhizal (AM) fungi can determine their fitness under specific environmental conditions, although knowledge of the underlying mechanisms still is very fragmented. Here we compared seven homokaryotic isolates (genotypes) of Rhizophagus irregularis, aiming to characterize the range of intraspecific variability with respect to hyphal exploration of organic nitrogen (N) resources, and N supply to plants. To this end we established two experiments (one in vitro and one in open pots) and used 15N-chitin as the isotopically labeled organic N source. In Experiment 1 (in vitro), mycelium of all AM fungal genotypes transferred a higher amount of 15N to the plants than the passive transfer of 15N measured in the non-mycorrhizal (NM) controls. Noticeably, certain genotypes (e.g., LPA9) showed higher extraradical mycelium biomass production but not necessarily greater 15N acquisition than the others. Experiment 2 (in pots) highlighted that some of the AM fungal genotypes (e.g., MA2, STSI) exhibited higher rates of targeted hyphal exploration of chitin-enriched zones, indicative of distinct N exploration patterns from the other genotypes. Importantly, there was a high congruence of hyphal exploration patterns between the two experiments (isolate STSI always showing highest efficiency of hyphal exploration and isolate L23/1 being consistently the lowest), despite very different (micro) environmental conditions in the two experiments. This study suggests possible strategies that AM fungal genotypes employ for efficient N acquisition, and how to measure them. Implications of such traits for local mycorrhizal community assembly still need to be understood.
Keywords: houby; genotyp; Stable isotopic labeling and tracing; Intraspecific differences; Genotype; hyfy; Chitin; dusík; Quantitative real-time PCR (qPCR); Fungi; Hyphae; Mycorrhizae; mykorhiza; chitin; Hyphosphere microbiome; Glomeromycota; Mycorrhizal hyphal networks; Soil nitrogen exploration; Nitrogen